Performansi Alat Pengering Tenaga Surya Pemanasan Langsung Dengan Kombinasi Penyimpan Panas - Delpanro Sitanggang; Azridjal Aziz; Herisiswanto Herisiswanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Solar dryer is a drying foodstuffs, agricultural products and fishery products with the aim of accelerate the drying process using solar energy. This research is aims to find out the performance of the dryer with heat storage on the reduction of the water content of the material. This tool is combined with a heat storage system using a split stone material or so-called rock beds as a sensible heat storage medium to dry raja sere bananas. The drying process is carried out for 8 hours with direct heating from solar thermal energy and continued for 4 hours by utilizing heat from the heat storage system. The test parameters include the intensity of solar radiation, temperature, and the decrease of material mass. The average solar intensity received by the solar collector is 882.39 W/m2, with an average material temperature of 34.02°C. The highest temperature on rack 8 is 35.09oC and the lowest temperature in rack 1 is 33.25oC. The highest rock temperature of 43.94oC with thermal energy is stored at 2311.87 kJ. Percentage reduction of material mass by 39.59% with final moisture content of 45% wet basis.Keywords: Solar Dryer, Heat Storage, Mass Reduction.